Schaums outline of theory and problems of calculus of : finite differences and difference equations - Murray R Spiegel (New York McGraw Hill Education India Pvt Ltd, 2020)
This powerful study tool covers difference calculus, sum calculus, difference equations and more With many examples of their applications. Ideal for solo study or as a supplement to a course, it clearly explains principles and theorems and gives definitions, then takes students through problems and their step-by-step solutions. This provides firm footing and excellent preparation for real-life problems and school examinations.
Keywords: Sum Calculus; Difference Equations